2020
DOI: 10.1038/s41388-020-1280-x
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations in the DNA repairome in prostate cancers in African Americans and Caucasians

Abstract: Most hereditary tumors show aberrations in DNA repair genes or their regulators. In contrast, only a minority of sporadic tumors show alterations in these genes. As a result, genomic instability is currently considered an enhancer of tumorigenesis rather than an obligatory event in this process. However, tumor heterogeneity presents a significant technical challenge for most cancer genomics studies performed at less than 100× mean resolution depth. To address the importance of genomic instability in prostate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…Research has suggested there may be important differences between African-American men with PC versus Caucasian men. [35][36][37][38] Additionally, NCCN guidelines recommends Ashkenazi Jewish population for genetic testing. 5 Studies lacked consistency for the specific HRRm assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested there may be important differences between African-American men with PC versus Caucasian men. [35][36][37][38] Additionally, NCCN guidelines recommends Ashkenazi Jewish population for genetic testing. 5 Studies lacked consistency for the specific HRRm assessed.…”
Section: Discussionmentioning
confidence: 99%
“…A proposed feature of prostate tumors in African American men that may play a prominent role in differential response to treatment is a deficiency in DNA damage repair capacity. Both germline and somatic alterations to DNA damage repair pathways have now been found in prostate tumors across multiple studies [66,[105][106][107]. Tumors from African American men were reported to have a significantly lower level of DNA repair capacity when compared to those from European American men.…”
Section: Germline and Somatic Mutations In Dna Repair Pathwaysmentioning
confidence: 99%
“…Genomic instability contributes to tumorigenesis and both germline and somatic mutations are amenable to novel therapeutic approaches. Somatic mutations of DNA repair and response mechanisms in PCa patients differ between AA and EA populations [ 66 ]. Although mutations of major DNA pathways were present in both AA and EA PCa tumors, AA men had a larger number of somatic mutations [ 66 ].…”
Section: Race Tme and Tumor Sitementioning
confidence: 99%
“…Somatic mutations of DNA repair and response mechanisms in PCa patients differ between AA and EA populations [ 66 ]. Although mutations of major DNA pathways were present in both AA and EA PCa tumors, AA men had a larger number of somatic mutations [ 66 ]. The consequences of these somatic alterations in cancer cells (or premalignant epithelial cells) on neighboring stromal partners including fibroblasts are currently not known.…”
Section: Race Tme and Tumor Sitementioning
confidence: 99%